Failure of first meningococcal vaccination in patients with atypical haemolytic uraemic syndrome treated with eculizumab. Issue 2 (9th July 2018) - Gäckler, Anja; Kaulfuß, Meike; Rohn, Hana; Vogel, Ulrich; Claus, Heike; Feldkamp, Thorsten; Kribben, Andreas; Witzke, Oliver
Abstract: Background: The C5 complement inhibitor eculizumab is a first-line treatment in atypical haemolytic uraemic syndrome (aHUS). Therapy with eculizumab is associated with a highly increased risk for meningococcal infection. Therefore, vaccination is highly recommended before beginning treatment. Efficacy of quadrivalent meningococcal vaccines (MenACWY) in patients treated with the C5 complement inhibitor eculizumab in aHUS has not yet been determined. Methods: Patients with aHUS received one dose of a MenACWY conjugate vaccine before eculizumab treatment commenced. Bactericidal titres against meningococcal serogroups A, C, W and Y were determined using baby rabbit complement in 25 patients. Results: Full immune response to meningococcal vaccination was detected in five patients (20%), while seven patients (28%) showed no immune response in any of the tested serogroups. The remaining 13 patients showed incomplete immune response with proof of protective antibody titres for one to three serogroups without perceptible preference for any serogroup. Bactericidal titres after re-vaccination were available for 17 patients. Nine patients with incomplete immune response after first vaccinations showed protective antibody titres for all serogroups after re-vaccination. Kidney function had improved in >50% of patients at the time of re-vaccination compared with the time of first vaccination and immunosuppressive therapy was only applied to re-vaccinated patients following kidney transplantation. Conclusions: Immunogenicity of first quadrivalent meninongococcal vaccination is insufficient in patients with aHUS. Booster response is promising, but incomplete. Therefore, establishing antibiotic prophylaxes seems pivotal.